Intellectual Capital Management in Digital Healthcare. Intellectual Property Strategies for Smart Dressings - Eriksson, Lovisa; Thunholm, Susanna (My University, 2019)
Wound care is a segment in medical technology that is becoming increasingly important to improve as we are due to our modern lifestyle more prone to acquire wounds. An increased incidence of diabetes, obesity and cardiovascular diseases as well as an ageing population are factors increasing the risks. Today, five to seven million people in the US acquire chronic wounds annually, which corresponds to treatment costs up to $20 billion. Market trends implicate that the wound care segment will be impacted and innovated by digital transformation, just like any other segment in healthcare, and the technology of smart dressings could be the next innovation that addresses the difficult challenges in advanced wound care. Smart dressings are wound dressings with the purpose to monitor certain wound characteristics, which will be processed to provide an output for treatment recommendations or actions. Smart dressings comprise the dressing as such, but is also connected to a network where data can be exchanged, processed and stored. The measured wound characteristics will thus be analyzed to either give an indication of the progression of the wound healing or provide for a treatment adapted to the wound characteristics. This thesis investigates whether a global actor that operates within wound care has the intellectual assets and properties to create and control a smart dressing. The research focused on the current status of the market, which showed an immaturity with no launched products, and the patent landscape, that presented a scarcity of relevant patents, a majority of pending patents. The patent landscape could be seen as a field that combines two mature and dense patent fields - wound dressings and electronics. Therefore, it could be considered difficult to obtain patent protection as the threshold for genericity is low for both of the mature fields, hence, the technical scope needs specificity to achieve patent eligibility. A knowledge gap was discovered in the patent landscape that revealed an uncertainty of what wound characteristic to measure, which could be an opportunity to leverage on if one learn what parameter is the most crucial for wound healing progression. The patent landscape was complemented by a value chain analysis to examine opportunities of value creation, which resulted in value propositions for patients of improved wound treatment and data generated value propositions of e.g. personalized care and product development opportunities. The current situation of the market and patent landscape together with the opportunities of value creation, could be leveraged on if the right capabilities are achieved in combination with suitable control mechanisms. An intellectual property strategy could and should include patent protection of the smart dressing system with physical components and software implemented functions. The functions enabling management of the generated data are eligible for other intellectual property rights, such as copyright, trademark, design and trade secrets.